2021
DOI: 10.1007/s00170-021-08201-0
|View full text |Cite
|
Sign up to set email alerts
|

Laser additive remanufacturing parameters optimization and experimental study of heavy-duty sprocket

Abstract: Experimental research on laser additive remanufacturing technology of heavy-duty sprocket was carried out. The influences of laser power, scanning speed and powder feeding rate on cladding height, cladding area, melting area and dilution rate were compared and analyzed. The prediction models of the combination of process parameters with the geometric characteristics of cladding layer and dilution were established. A multi-objective process parameter optimization model with the maximum cladding height and cladd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The unreasonable selection of laser process parameters such as laser power, scanning speed, and powder feeding rate is the main reason for the poor forming characteristics of the cladding layer [9]. Scholars have carried out a lot of research on various methods to optimize the process parameters of laser cladding, including the response surface method (RSM) [10][11][12], grey relational analysis [13,14], optimization algorithm [15], and linear regression method, etc. [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unreasonable selection of laser process parameters such as laser power, scanning speed, and powder feeding rate is the main reason for the poor forming characteristics of the cladding layer [9]. Scholars have carried out a lot of research on various methods to optimize the process parameters of laser cladding, including the response surface method (RSM) [10][11][12], grey relational analysis [13,14], optimization algorithm [15], and linear regression method, etc. [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The grey correlation value increased by 0.229 under optimal conditions. Guo et al [15] established a multi-objective optimization model based on the maximum cladding height and cross-section area, minimum heat-affected zone area, and dilution rate, and further optimized the solution by the MOPSO algorithm. They concluded that the model has higher prediction accuracy, in addition, the scanning speed and powder feeding rate had a significant influence on the dilution rate and the geometric characteristics of the cladding layer.…”
Section: Introductionmentioning
confidence: 99%